RETRACTED : The Effect of Compensation, Effectiveness of Communication and Promotion, on Employee Performance, PT. Artistic Creations Globalindo, Bekasi - Mohammad Rizki Saputra; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze how strong the influence of Compensation, Communication Effectiveness, and Promotion on Employee Performance partially, this research was conducted at PT. Globalindo Artistic Creations, Bekasi. This study was conducted using primary data obtained from the distribution of questionnaires, a population of 140 employees with a sample of 104 respondents. Management of analytical data using validity and reliability tests as well as regression and correlation tests using SPSS 20. Based on the results of the study, multiple regression equations Y = 1.034 + 0.233 X1 + 0.250 X2 + 0.492 X3 + e The results showed that Compensation (X1) has a positive influence on employee performance (Y), Communication Effectiveness (X2) has a positive influence on employee performance (Y) and Promotion Against (X3) has a positive influence on employee performance (Y). The result of the correlation between Compensation, Communication Effectiveness, and Promotion on employee performance (Y). And the results of the F Test of Compensation, Communication Effectiveness, and Promotion together have a positive and significant effect on Employee Performance